ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA PEMERINTAH KOTA MAGELANG GUNA PENINGKATAN PELAYANAN PUBLIK - Ariyanti, Nadya Wahyu; Ratnawati, Shinta (JAB (Jurnal Akuntansi & Bisnis), 2020)
ABSTRACTÂ This study aims to describe the development of human resources in the City Government of Magelang in order to improve better public services. This research uses qualitative methods with data collection techniques such as interviews, observation, and documentation. The results of this study indicate that the Development of Government Apparatus resources in the Government of Magelang City in order to improve good public services for the community through education and training activities has been carried out continuously and has been adjusted to the needs of work in accordance with their respective levels. Magelang City Government uses the on the job method in developing its human resources. Education and training that is often held by the City Government of Magelang are basic education and training for CPNS and in-service education and training for employees consisting of leadership, functional and technical education and training.Â Keyword: development, education and training, public service.